Outside/inside: social determinants of mental health. (30th March 2023) - Gnanapragasam, Sam Nishanth; Astill Wright, Laurence; Pemberton, Max; Bhugra, Dinesh
Abstract : Individuals' mental health and wellbeing are dependent on many social factors including housing, employment, education and adequate nutrition among others. These factors can influence at personal, family and community levels. The interlinked and cumulative impact of these social determinants needs to be ascertained to aid appropriate patient management, as well as to establish prevention and health education programmes. Some of these determinants also have to be recognised at policy level. It is crucial for clinicians to understand the role social determinants play in the genesis and perpetuation of mental and physical illnesses, so that appropriate social interventions can be set in place. Clinicians have a role to play in their clinical practice, as well as advocates for their patients and policy leaders. In order to ensure that health is joined up with other sectors, such as education, employment, judiciary and housing, policy-makers must avoid silos. Every policy must have an impact assessment on physical health and mental health. Policy-makers need to understand scientific evidence and must work with researchers, clinicians, communities and patients to help develop and implement rights-based policies.